Consumer Preferences and Opportunity Costs in Local Culture: A Microeconomic Analysis of Wangkar Walek Song Lyrics - Vianney, Yohanes Mario; Larum, Kordianus (West Science Interdisciplinary Studies, 2025)
Regional songs not only hold aesthetic and cultural values, but also contain socio-economic reflections of the community. The song Wangkar Walek from Manggarai is one form of cultural expression that contains narratives about choices, sacrifices, and social relations in the context of romance. Within the framework of microeconomics, the story in this song can be understood as a real picture of how individuals make decisions in situations of limitations and complex social considerations. The lyrics show individual preferences that are not only based on material gains, but also on emotional and social values such as love, recognition and dignity. On the other hand, there are real opportunity costs when the characters in the song have to sacrifice other alternatives that may be more socially or economically beneficial. These choices cannot be separated from the strong influence of local culture, such as customary norms, social status, and family expectations that shape the economic framework of traditional society. This research uses a descriptive qualitative approach with content analysis techniques of Wangkar Walek song lyrics. Data were obtained from song texts as primary sources, as well as literature on microeconomics and Manggarai culture as secondary sources. The results show that consumer preferences and opportunity costs are not only present in the modern market space, but also in the social interactions of traditional communities recorded in cultural works. This research opens an integrative space between economic studies and local culture, and becomes a contextual approach in microeconomic education.